Membangun Karakter Positif Dalam Pendidikan: Tantangan Dan Strategi Dalam Perspektif Psikologi Pendidikan - Fauziah Nasution; Gadis Anggun Fitrah; Hawa Alfina; Muhammad Faisal Hajmi (IJIGAEd: Indonesian Journal of Islamic Golden Age Education, 2023)
The main goal of education is to build positive character in individuals. However, there are significant challenges in forming positive character. This article discusses the challenges and strategies in building positive character in education from the perspective of educational psychology. Strategies such as positive character education and cooperative learning models can help build positive student character. Support from the social environment, collaboration between educators and parents, as well as exploration of effective communication functions are also important in forming positive character. This article provides important information for educators on how to improve methodology and create a positive social learning environment.